A Journey to the Other Side of the World on an Unknown Itinerary - Castleden, Susanna (Rowman & Littlefield International, 2016)
The book opens a space for experiential appreciation by offering a writing that allows both the writer and the reader to consider those sorts of embodied sensibilities